The Relation Between Union Wage Impact and Market Structure - Segal, Martin (Quarterly Journal of Economics, 1964)
I. Introduction, 96. — II. Two preliminary matters: union wage policies, 97; elements of market structure, 98. — III. Basic links between market structure and union ability to make wage gains in four types of industries, 100. — IV. Other aspects of market structure that affect union policies and their impact on wages, 111. — V. Conclusion, 113.